2020
DOI: 10.21203/rs.3.rs-40114/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Review on Wearable Lower-Limb Exoskeletons for Gait Training in Neuromuscular Impairments

Abstract: Gait disorders can reduce the quality of life for people with neuromuscular impairments. Therefore, walking recovery is one of the main priorities for counteracting sedentary lifestyle, reducing secondary health conditions and restoring legged mobility. At present, wearable powered lower-limb exoskeletons are emerging as a revolutionary technology for robotic gait rehabilitation. This systematic review provides a comprehensive overview on wearable lower-limb exoskeletons for people with neuromuscular impairmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 46 publications
0
20
0
3
Order By: Relevance
“…A motorized exoskeleton with a user can be modeled as a four-link bipedal walking system in the sagittal plane as follows M (q)q + C(q, q) q + G(q) + P (q, q) + d(t) = τ e (q, q, t), (1) where q : R ≥t0 → R 4 denotes the measurable hip and knee joint angles on both sides, q, q : R ≥t0 → R 4 denote the measurable joint angular velocities and unmeasurable joint angular accelerations, respectively, where t 0 ∈ R >0 is denoted as initial time; M : R 4 → R 4×4 >0 denotes the combined human-exoskeleton inertia; C : R 4 × R 4 → R 4×4 and G : R 4 → R 4 denote centripetal-Coriolis and gravitational effects, respectively; P : R 4 ×R 4 → R 4 denotes the damping and viscoelastic effects; and d : R ≥t0 → R 4 denotes unmodeled terms and disturbances. The torque produced by the electrical motors are expressed as τ e : R 4 ×R 4 ×R ≥t0 → R 4 .…”
Section: Human-exoskeleton Dynamic Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…A motorized exoskeleton with a user can be modeled as a four-link bipedal walking system in the sagittal plane as follows M (q)q + C(q, q) q + G(q) + P (q, q) + d(t) = τ e (q, q, t), (1) where q : R ≥t0 → R 4 denotes the measurable hip and knee joint angles on both sides, q, q : R ≥t0 → R 4 denote the measurable joint angular velocities and unmeasurable joint angular accelerations, respectively, where t 0 ∈ R >0 is denoted as initial time; M : R 4 → R 4×4 >0 denotes the combined human-exoskeleton inertia; C : R 4 × R 4 → R 4×4 and G : R 4 → R 4 denote centripetal-Coriolis and gravitational effects, respectively; P : R 4 ×R 4 → R 4 denotes the damping and viscoelastic effects; and d : R ≥t0 → R 4 denotes unmodeled terms and disturbances. The torque produced by the electrical motors are expressed as τ e : R 4 ×R 4 ×R ≥t0 → R 4 .…”
Section: Human-exoskeleton Dynamic Modelmentioning
confidence: 99%
“…Powered exoskeletons vary in their design, wearability, sensing, and actuation. Existing powered exoskeletons use electrical motors [1], hydraulic [2] and pneumatic actuators [3], [4]. The actuators used to outfit the exoskeleton influence the magnitude and response of the inputs applied to the body and thus the human-robot interaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High variability was found in the number of partici-702 pants (14.87 ± 13.53), number of sessions (11.77 ± 12.20),703 session frequency (times per week; 3.09 ± 1.68), and 704 session duration (50.57 ± 34.06 min) (see Figure 5.C). 705 Previous reviews that analyzed the protocol of robotic 706 treatment reported similar high variability [40,46]. 707 Some studies did not provide complete information 708 about the experimental protocol, e.g., they did not mention the number (15.09 %), duration (33.33 %), or frequency (31.44 %) of the training sessions.…”
mentioning
confidence: 99%